FACTORS AFFECTING STUDENTS’ MOTIVATION IN ONLINE CLASS - Nuriyatul Hamidah (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
Some components of learning environment might affect learner behaviors during the teaching and learning process in both face-to-face and virtual learning environments. One of those components is students’ motivation which is the best variable that affects students’ learning. Research literature consistently suggests that EFL (English as a foreign language) students’ motivation is affected by some teaching factors (Lamb, 2017). This study aims at determining the factors that increase students’ motivation in their online courses at higher education levels. In this framework, the students who were in the fourth and sixth semesters were asked to explain their opinions about the factors increasing their motivation and what can be done to increase their motivation. The students have been having online classrooms for almost four semesters. The writer employs qualitative research as the method to conduct this study. To collect the data, an interview guide is designed. Then, the research results show that the teaching- learning process, teacher’s competency, students’ engagement, online learning environment/technical infrastructure and time management could affect students’ motivation in their online courses. Besides, it is also stated that interactive assessment and evaluation would increase their motivation.